2013
DOI: 10.1111/php.12120
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Carbene Equilibria

Abstract: Reviewed herein are equilibria between halocarbenes and halocarbanions, carbenes and carbene complexes and carbenes and O-ylides. The transient species were visualized by laser flash photolysis coupled with UV-Visible spectroscopy. This methodology enabled the determination of equilibrium constants and the extraction of associated thermodynamic parameters. Parallel computational studies provided anticipated structures and energies for the transient species, as well as electronic absorption wavelengths and osci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…These experimental observations were found to be consistent with the results of theoretical calculations Remarkably, although time-resolved laser flash photolysis (LFP) has played a critical role in studying various types of carbenes, there appear to be no reports attesting to the use of this method for the investigation of alkylidenecarbenes. Perhaps this conspicuous void in the literature may be attributed to the lack of photochemical precursors suitable for such studies.…”
Section: Introductionsupporting
confidence: 65%
“…These experimental observations were found to be consistent with the results of theoretical calculations Remarkably, although time-resolved laser flash photolysis (LFP) has played a critical role in studying various types of carbenes, there appear to be no reports attesting to the use of this method for the investigation of alkylidenecarbenes. Perhaps this conspicuous void in the literature may be attributed to the lack of photochemical precursors suitable for such studies.…”
Section: Introductionsupporting
confidence: 65%
“…Recent studies have shown that once generated, ground state singlet carbenes can be temporarily stabilized by means of the formation of meta-stable complexes with solvent molecules having nonbonding electrons (examples: oxygen atoms in ethers or alcohols) or p electrons (examples: benzene, aromatic rings). [11][12][13] The stabilization would occur through the interaction between the excess electron density in solvent molecules and the empty p-like orbital in the carbene carbon atom. 14 Singlet carbenes can be generated from photolysis of diazirines 15,16 using laser flash photolysis (LFP).…”
Section: Introductionmentioning
confidence: 99%
“…LFP of dichlorodiazirine in 1:1 MeCN−CH 2 Cl 2 solution containing 0.9 M TBACl affords a weak absorbance for CCl 3 − at 328 nm in accord with the reverse of eq 8. 53,54 Unfortunately, the equilibrium constant (K) could not be determined because the absorbance of CCl 2 in the solution is too weak under our LFP conditions. An indirect determination of K ∼ 10 M −1 is possible for the equilibrium of eq 9 involving CCl 2 Br − (388 nm).…”
Section: Diazirine-exchange Reaction and Derived Carbenesmentioning
confidence: 99%